Colloidal Nutrition Improves Parameters of Pecan Tree (Carya illinoinensis) Soil Health Such as Organic Matter, Available Water, and Electrical Conductivity - Rubén Gerardo León-Chan; Brandon Estefano Morales-Merida; Luis Amarillas; Nancy Varela-Bojórquez; Luis Alberto Lightbourn-Rojas (Agriculture)
Background: Soil degradation and nutrient depletion critically impact pecan (Carya illinoinensis) production, reducing yield and soil fertility. Colloidal nutrition, a novel approach involving nano-scale nutrient formulations, could offer potential for soil restoration. Aim: This study aimed to assess the impact of colloidal nutrition on key physical, chemical, and biological soil health parameters in pecan tree cultivation. Methods: Soil from two orchards with 30-year-old pecan trees was used where different nutrition treatments were applied: conventional and colloidal. The variables considered included physical, chemical, and biological properties for the assessment of soil health indicators. Results: The colloidal treatment showed low salinity (2020: 2.04; 2021: 0.88 dS/m) and higher levels of humic acids (1.52 g C/100 g soil), available water depth (2020: 305.11, 2021: 350.00 m3/ha), and soil organic matter (2020: 2.10%; 2021: 2.11%). Furthermore, 6 of the 17 phytopathogens that were examined were not detected in the colloidal treatment. Conclusions: This study enhanced our understanding of the improvements that colloidal treatment could potentially provide to the physical, chemical, and biological aspects of soil health in pecan orchards.